Self-delivering prodrug-nanoassemblies fabricated by disulfide bond bridged oleate prodrug of docetaxel for breast cancer therapy - Shenwu Zhang; Jibin Guan; Mengchi Sun; Dong Zhang; Haotian Zhang; Bingjun Sun; Weiling Guo; Bin Lin; Yongjun Wang; Zhonggui He; Cong Luo; Jin Sun (Taylor & Francis Group, 2017)
Breast cancer leads to high mortality of women in the world. Docetaxel (DTX) has been widely applied as one of the first-line chemotherapeutic drugs for breast cancer therapy. However, the clinical outcome of DTX is far from satisfaction due to its poor drug delivery efficiency. Herein, a novel disulfide bond bridged oleate prodrug of DTX was designed and synthesized to construct self-delivering prodrug-based nanosystem for improved anticancer efficacy of DTX. The uniquely engineered prodrug-nanoassemblies showed redox-responsive drug release, increased cellular uptake and comparable cytotoxicity against 4T1 breast cancer cells when compared with free DTX. In vivo, oleate prodrug-based nanoparticles (NPs) demonstrated significantly prolonged systemic circulation and increased accumulation in tumor site. As a result, prodrug NPs produced a notable antitumor activity in 4T1 breast cancer xenograft in BALB/c mice. This prodrug-based self-assembly and self-delivery strategy could be utilized to improve the delivery efficiency of DTX for breast cancer treatment.